Deciphering CHFR Role in Pancreatic Ductal Adenocarcinoma - González-Borja, Iranzu; Alors-Pérez, Emilia; Amat, Irene; Alonso, Laura; Viyuela-García, Cristina; Goñi, Saioa; Reyes, José C.; Ceballos-Chávez, María; Hernández-García, Irene; Sánchez-Frías, Marina E.; Santamaría, Enrique; Razquin, Socorro; et al. (Frontiers in Medicine, 2021)
CHFR has been proposed as predictive and prognosis biomarker for different tumor types, but its role in PDAC remains unknown. The aim of this study was two pronged: reviewing the role of CHFR in PDAC, and to evaluate CHFR as potential predictive biomarker in this disease. For this purpose, we first explored CHFR mRNA expression and promoter methylation through TCGA database. Secondly, CHFR expression and promoter methylation were prospectively evaluated in a cohort of patients diagnosed with borderline (n=19) or resectable (n=16) PDAC by immunohistochemistry (IHC), Methylation Specific-PCR (MSP) and pyrosequencing. Results from TCGA database showed significant differences in terms of PFS and OS based on CHFR mRNA expression, which was likely independent from promoter methylation. Importantly, our results showed that, in primarily resected patients but also in the entire cohort, higher CHFR expression as indicated by higher IHC staining intensity might identify patients with longer DFS and OS, respectively. Similarly, in the same cohorts, patients with lower methylation levels by Pyrosequencing showed significantly longer OS than patients without this pattern. Both, CHFR expression intensity and its promoter methylation were established as independent prognostic factors for PFS and OS in the entire cohort. In contrast, no significant differences were found between different methylation patterns for CHFR and response to taxane-based neoadjuvant treatment. These results suggest the potential role of higher expression of CHFR and methylation pattern of its promoter as potential prognostic biomarkers in PDAC, thus warranting further comprehensive studies to extend and confirm our preliminary findings.